Simulation of an Indirect Rotor Flux Oriented Induction Motor Drive using Matlab/Simulink - Vivek V. Puranik; Vijay N. Gohokar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
Indirect Field Oriented Control (IFOC) is very popular technique in industries due to its simple designing and structure, in comparison to the direct method since it requires flux and torque estimators. This paper presents detail calculation of all values needed for the development of an indirect rotor flux oriented induction motor model fed by a current-controlled voltage source inverter. With the calculated values for 1 hp 50 Hz 3 phase induction motor; an indirect rotor flux oriented model is developed using MATLAB/Simulink. The simulation results are outlined and discussed.